A Study on the Taxation System in India and its Impact on the Economic Growth - Thomas , Joy (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this paper is to discuss the taxation system that is followed in India and its impact on Indian economic development. Government considers the tax as an important source of revenue and also major factor that decides the economic growth. Taxes are of two types, direct and indirect taxes. Direct tax works on the disposable income and the indirect tax works on the sale of goods and services. Direct tax has the components of personal income tax and corporate income tax. Indirect taxes consists of excise duty, customs duty etc. Government and policy makers should take a call on which tax is to be targeted to improve the economic growth in the country.